Hedging When Applying: Simultaneous Search with Correlation - Ali, S. Nageeb; Shorrer, Ran I. (American Economic Review, 2025)
Applicants to schools, colleges, and jobs hedge by applying to a broad range of options, including reaches, matches, and safeties. We develop a simultaneous-search framework that rationalizes this practice. In this framework, the admissions process is correlated across schools so that if an applicant is rejected by one school, she is more likely to be rejected by more selective schools. We find that an applicant then optimally targets both safeties and reaches. We characterize how the optimal portfolio varies with the applicant’s beliefs, risk attitudes, and application costs and offer an algorithm that delivers the optimal portfolio in polynomial time. (JEL D81, D83, D91, I23)